Bodies that Danced their Voices - Biancalana (Universidade Federal de Santa Maria – UFSM, Santa Maria/RS, Brazil), Gisela Reis (Revista Brasileira de Estudos da Presença, 2022)
The article makes a reflection about the relevance of the voice perceived as body in movement. This understanding is first discussed under the light of the assumptions of authors from performing arts, theater and dance. Next, it was made a proposal for a creative process in dance which considered the collaboration of performers on their path. Dance work was developed with actors and it had the voice as the main driving element. This artwork aimed to discuss a possible move towards a vocal pedagogy for the scene performers.